¿Acción y malestar? : las tácticas de resistencia de los menores internados en las instituciones asistenciales - Osorio Ballesteros, Abraham (El Colegio de México, 2014)
Based on a qualitative research in two public institutions care, this article discusses some of the tactics used by children placed to weather the relations with the authorities, avoid certain tasks and appropriate the space organized according to their needs and certain explicit resistance to indicate their disagreement with personnel actions they consider unfair. The text recognizes the creativity of children, so it takes up the theoretical contributions of De Certeau, Goffman and Moore to account, by way of example, both the logic that each point as the time when the handled. The paper concludes with three ideas that resemble the characteristics of these tactics and resistances and the ability of children.